Current State of Forest Resources in Guinea-Bissau - Nantunguê, Fernando; Sergeevna, Ershova Tatyana (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
The article examines the ecological state of forest resources in Guinea-Bissau, a country that possesses approximately 2–3 million hectares of forests encompassing diverse ecosystems, including sub-humid and dry forests, gallery forests, savannas, palm groves, and mangrove formations. Forest resources provide significant energy wood, consisting of an estimated 650,000 tons of firewood annually for domestic use and about 137,000 tons of charcoal. However, these resources face considerable anthropogenic and natural pressures. Forest fires, intensive logging, pest infestations, heavy metal accumulation, land degradation from mining, industrial and transport emissions, and excessive recreational exploitation are among the main factors negatively affecting forest stability. Current assessments indicate that Guinea-Bissau’s forested area covers 2,080,284 hectares, with bush savannah dominating (1,503,534 ha), followed by open forests (706,998 ha), mangroves (290,482 ha), and dense forests (65,775 ha). Forest pathological monitoring shows that 67.5% of forest stands remain healthy (condition category ≤1.5), while 31.9% exhibit reduced stability (condition category 1.5–4.5), with common pathologies including fusarium infections, root rot, leaf chlorosis, and necrosis. Key drivers of forest decline include logging for fuelwood and charcoal production, agricultural expansion–related deforestation, and both natural and human-induced fires. In 2019 alone, forest fires burned 44,336.7 hectares in Bafata and 38,701.5 hectares in Gabu. Overall, the findings underscore the urgent need for integrated forest management strategies to safeguard Guinea-Bissau’s vulnerable forest ecosystems.